Caffeine ingestion acutely enhances muscular strength and power but not muscular endurance in resistance-trained men - Grgic, J.; Mikulic, P. (European Journal of Sport Science, 2017)
The goal of this randomized, double-blind, cross-over study was to assess the acute effects of caffeine ingestion on muscular strength and power, muscular endurance, rate of perceived exertion (RPE), and pain perception (PP) in resistance-trained men. Seventeen volunteers (mean ± SD: age = 26 ± 6 years, stature = 182 ± 9 cm, body mass = 84 ± 9 kg, resistance training experience = 7 ± 3 years) consumed placebo or 6 mg kg-1 of anhydrous caffeine 1 h before testing. Muscular power was assessed with seated medicine ball throw and vertical jump exercises, muscular strength with one-repetition maximum (1RM) barbell back squat and bench press exercises, and muscular endurance with repetitions of back squat and bench press exercises (load corresponding to 60% of 1RM) to momentary muscular failure. RPE and PP were assessed immediately after the completion of the back squat and bench press exercises. Compared to placebo, caffeine intake enhanced 1RM back squat performance (+2.8%; effect size [ES] = 0.19; p = .016), which was accompanied by a reduced RPE (+7%; ES = 0.53; p = .037), and seated medicine ball throw performance (+4.3%, ES = 0.32; p = .009). Improvements in 1RM bench press were not noted although there were significant (p = .029) decreases in PP related to this exercise when participants ingested caffeine. The results point to an acute benefit of caffeine intake in enhancing lower-body strength, likely due to a decrease in RPE; upper-, but not lower-body power; and no effects on muscular endurance, in resistance-trained men. Individuals competing in events in which strength and power are important performance-related factors may consider taking 6 mg kg-1 of caffeine pre-training/competition for performance enhancement.